Administration of Dexrazoxane Improves Cardiac Indices in Children and Young Adults With Acute Myeloid Leukemia (AML) While Maintaining Survival Outcomes. Issue 5 (July 2017) - Schloemer, Nathan J.; Brickler, Molly; Hoffmann, Raymond; Pan, Amy; Simpson, Pippa; McFadden, Vanessa; Block, Joseph; Tower, Richard L.; Burke, Michael J.
Abstract : Anthracycline-induced cardiotoxicity remains a significant contributor to late morbidity/mortality in children and young adults with acute myeloid leukemia (AML). The cardioprotectant dexrazoxane can be used as prophylaxis to diminish risk for cardiomyopathy but whether it affects risk of relapse in pediatric AML is unclear. Our institution adopted the use of dexrazoxane before anthracyclines administration for all oncology patients in 2011. We compared patients with AML (ages, 0 to 21 y) who received or did not receive dexrazoxane during the years 2008 to 2013. In total, 44 patients with AML (ages, 4.5 mo to 21.7 y) were included. We identified no statistical difference in 2-year event rate (62% vs. 50%, P =0.41) or 2-year overall survival (69% vs. 69%, P =0.53) between patients receiving (n=28) or not receiving (n=16) dexrazoxane. Ejection fraction ( P =0.0262) and shortening fraction ( P =0.0381) trended significantly higher in patients that received dexrazoxane compared with those that did not receive dexrazoxane. Utilization of the cardioprotectant dexrazoxane before anthracycline chemotherapy in pediatric patients with AML demonstrated no significant difference in either event rate or overall survival relative to institutional controls and seems to improve cardiac function indices. Further studies in this patient population are needed to confirm these findings.